Integrated toxicology of Aconitum carmichaelii Debx.: bridging traditional toxicity-efficacy understanding and modern toxicology - Li, Xin-Yu; Zhou, Li; Jiang, Zhen-Hong; Liang, Yong; Fan, Ya-Guo; Ding, Zhao-Hui; Chen, Hao; Liu, Wen-Jun; Zhou, Xiang; Xu, Huan-Hua (Frontiers in Pharmacology, 2025)
Toxicity has different meanings in traditional Chinese medicine (TCM) and modern toxicology. Integrative toxicology, a novel discipline proposed by our team, offers a robust solution for the scientific elucidation of toxicity in traditional Chinese medicines. Aconitum carmichaelii Debx. (aconite), a classic herbal medicine with a long-standing TCM clinical application history, demonstrates prominent effects in rescuing yang to reverse critical conditions, warming meridians to dispel cold, and tonifying yang to invigorate qi. It is widely used to treat yang deficiency, cold syndromes, and related disorders. However, the dual toxicity-efficacy attribute of aconite has substantially constrained the safety and breadth of its clinical application, leading to its classification as a “high-risk herb.” Thus, this review introduces the concept of integrative toxicology to comprehensively summarize the chemical composition, pharmacological activity, and toxicity mechanisms of aconite. Particular emphasis is placed on various strategies and mechanisms for toxicity attenuation and efficacy enhancement within TCM formulae, including traditional approaches, such as processing and compatibility, as well as potential detoxification pathways identified in modern pharmacological studies. By systematically integrating the framework of integrative toxicology, this work aims to provide a more scientific and secure theoretical basis for the clinical application of aconite, promoting its transformation from a “high-risk herb” to a “controllable therapeutic agent” and thereby maximizing its potential value in modern medicine.